Style and the Future of Composition Studies - Butler, Paul (Utah State University Press, 2020)
""Many college writing teachers operate under the belief that style refers to issues discussed in Strunk and White's outdated book, The Elements of Style. This view is challenged and offers theories and pedagogies from diverse perspectives helping teachers and students develop strategic habits to negotiate languages, genres, and discourse conventions"--Provided by publisher"--